Intellectual property, antitrust and cumulative innovation in the EU and the US - Kaseberg, Thorsten (Hart studies in competition law, 2012)
This study addresses how 'cumulative innovation' is accounted for under IP and antitrust laws in the EU and US, and how it could alternatively be dealt with. Topics include policy levers under European and US patent, copyright and trade secrecy laws, compulsory licensing regimes and misuse documents